Customer value discovery - McKnight, Sue (Henry Stewart Talks, 2012)
Customer value discovery, Enzyme International, Library services, Customer satisfaction, Library performance measurement, Evidence based library & information practice, University library services, Academic library services, Perceptions of library performance, Interactive value modeling, Customer service excellence